2014
DOI: 10.1590/1413-78522014220200844
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between different radiographic methods for evaluating the flexibility of scoliosis curves

Abstract: OBJECTIVE: To compare different radiographic methods of spine evaluation to estimate the reducibility and flexibility of the scoliosis curves. METHODS: Twenty one patients with Lenke types I and III adolescent idiopathic scoliosis (AIS) were included. Radiographic evaluations were made preoperatively on the orthostatic, supine decubitus with lateral inclination to the right and left and supine positions with manual reduction, with support in the apex of each curve on the X-ray table. On the day of surgery, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…It should be noted that the after-general-anesthesia orthopedic effect was better at the traction radiograph than at the fulcrum radiograph when the interference of muscles and soft tissues was ruled out. This was echoed by studies of Rodrigues et al [ 17 ] Therefore, the orthopedic force applied in the longitudinal direction can still be regarded as superior to that in the cross-sectional direction. The reason why the flexibility achieved at the normal traction radiograph is not so good as at the fulcrum radiograph may be that the actual orthopedic force applied to the spine is smaller than the applied external force due to muscle tension during the process of traction.…”
Section: Discussionmentioning
confidence: 93%
“…It should be noted that the after-general-anesthesia orthopedic effect was better at the traction radiograph than at the fulcrum radiograph when the interference of muscles and soft tissues was ruled out. This was echoed by studies of Rodrigues et al [ 17 ] Therefore, the orthopedic force applied in the longitudinal direction can still be regarded as superior to that in the cross-sectional direction. The reason why the flexibility achieved at the normal traction radiograph is not so good as at the fulcrum radiograph may be that the actual orthopedic force applied to the spine is smaller than the applied external force due to muscle tension during the process of traction.…”
Section: Discussionmentioning
confidence: 93%
“…However, it has also been shown that selection of lowest instrumented vertebra based on traction radiographs leads to an increased frequency of decompensation of the non-instrumented lower spinal segments [10,17]. The available data show that none of the common types of BR is superior to the others [6,8,10,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BR allows assessing the possible potential for correction of the deformity by surgery [6,7]. There are different types of bending radiographs: Push-prone radiographs (PPR) [8], fulcrum bending radiographs [6], supine side-bending radiographs [9], and radiographs with traction under General Anesthesia [10]. All types of BR lead to an additional amount of exposure to radiation for the patient.…”
Section: Introductionmentioning
confidence: 99%
“…As regards the L curve, we noted that bending presented lower values than traction, (Table 3) a finding similar to the study by Watanabe et al, 15 which obtained a statistical difference when the initial Cobb angle was less than 50 o , as in our study in which the mean L curve found was 49.1 o . In the traction under anesthesia technique described by Davis et al, 6,8 in which muscle relaxation removes traction discomfort for the patients, a better result was obtained. In this study it was observed that this method had a greater absolute decrease in the mean curve, coinciding with Davis et al and Hamzaoglu et al, 10 (Tables 1, 2 and 3) being always less than bending and traction and closer to the postoperative values.…”
Section: Discussionmentioning
confidence: 99%
“…2 In their classifications, King 3 and Lenke 4 highlighted the importance of the flexibility of the curves in the radiographical examination, formulating the concept of curve structurality and defining it as one of the most important parameters for surgical planning, responsible for the choice of arthrodesis levels and the number of corrective osteotomies. [5][6][7][8][9] Flexibility can be analyzed by several methods: bending in the standing or dorsal horizontal decubitus positions, fulcrum bending, traction, traction under general anesthesia, among others. [5][6][7][10][11][12] Currently, bending radiographs are considered the gold standard for flexibility assessment, because they are easy to perform and are one of the parameters included in the classifications.…”
Section: Introductionmentioning
confidence: 99%